Does lobar or size-reduced lung transplantation offer satisfactory early and late outcomes? - Santos Silva, João (Interact Cardiovasc Thorac Surg, 2020)
A best evidence topic was constructed according to a structured protocol. The question addressed was whether size-reduced or lobar lung transplantation (LLTx) offers the same benefit as classic lung transplantation (LTx). Of the 147 papers found using the reported search, 9 were selected to provide the best evidence. Details of the studies regarding authors, date, journal, country of publication, study type, group studied, relevant outcomes and results are given. All studies reported survival rates of LLTx and most compared it with classical LTx. No statistical differences were reported in medium term and long term. Two of the studies reported a higher incidence of postoperative complications, such as the need for cardiopulmonary bypass, reperfusion oedema or primary graft dysfunction, and longer intubation or intensive care unit stay times. Although the largest study showed a significantly worse 1-year survival in LLTx, a sub-analysis considering patients successfully discharged showed similar outcomes at 1, 3 and 5 years when compared with classic LTx patients. We conclude that LLTx is a valid therapeutic option for recipients with significant donor size mismatch, offering similar outcomes as classical LTx in the medium term and long term.